Prevalence and associated risk factors of polycystic ovary syndrome in Asian countries - Eathan, Bodron Nesa; Mahmud, Ananya (Brac University, 2024)
A thesis submitted to the Department of Mathematics And Natural Science in partial fulfillment of the requirements for the degree of B.Sc. in Microbiology, 2022.